Tetrahydroisoquinolines affect the whole-cell phenotype of Mycobacterium tuberculosis by inhibiting the ATP-dependent MurE ligase. (4th February 2015) - Guzman, Juan D.; Pesnot, Thomas; Barrera, Diana A.; Davies, Heledd M.; McMahon, Eleanor; Evangelopoulos, Dimitrios; Mortazavi, Parisa N.; Munshi, Tulika; Maitra, Arundhati; Lamming, Eleanor D.; Angell, Richard; Gershater, Markus C.; et al.
Abstract: Objectives: ( S )-Leucoxine, isolated from the Colombian Lauraceae tree Rhodostemonodaphne crenaticupula Madriñan, was found to inhibit the growth of Mycobacterium tuberculosis H37 Rv. A biomimetic approach for the chemical synthesis of a wide array of 1-substituted tetrahydroisoquinolines was undertaken with the aim of elucidating a common pharmacophore for these compounds with novel mode(s) of anti-TB action. Methods: Biomimetic Pictet–Spengler or Bischler–Napieralski synthetic routes were employed followed by an evaluation of the biological activity of the synthesized compounds. Results: In this work, the synthesized tetrahydroisoquinolines were found to inhibit the growth of M. tuberculosis H37 Rv and affect its whole-cell phenotype as well as the activity of the ATP-dependent MurE ligase, a key enzyme involved in the early stage of cell wall peptidoglycan biosynthesis. Conclusions: As the correlation between the MIC and the half-inhibitory enzymatic concentration was not particularly strong, there is a credible possibility that these compounds have pleiotropic mechanism(s) of action in M. tuberculosis .